Peptide synthesis: ball-milling, in solution, or on solid support, what is the best strategy? - Maurin, Ophélie; Verdié, Pascal; Subra, Gilles; Lamaty, Frédéric; Martinez, Jean; Métro, Thomas-Xavier (Beilstein Journal of Organic Chemistry, 2017)
While presenting particularly interesting advantages, peptide synthesis by ball-milling was never compared to the two traditional strategies, namely peptide syntheses in solution and on solid support (solid-phase peptide synthesis, SPPS). In this study, the challenging VVIA tetrapeptide was synthesized by ball-milling, in solution, and on solid support. The three strategies were then compared in terms of yield, purity, reaction time and environmental impact. The results obtained enabled to draw some strengths and weaknesses of each strategy, and to foresee what will have to be implemented to build more efficient and sustainable peptide syntheses in the near future.
Keywords: ball-mill; green chemistry; mechanochemistry; peptide synthesis; SPPS

(untitled) - Vlieghe, P.; Lisowski, V.; Martinez, J.; Khrestchatisky, M. (Drug Discovery Today, 2010)

(untitled) - Albericio, F.; Kruger, H. G. (Future Med. Chem., 2012)

(untitled) - Fosgerau, K.; Hoffmann, T. (Drug Discovery Today, 2015)

(untitled) - Bray, B. L. (Nat. Rev. Drug Discovery, 2003)

(untitled) - Constable, D. J. C.; Dunn, P. J.; Hayler, J. D.; Humphrey, G. R.; Leazer, J. L., Jr; Linderman, R. J.; Lorenz, K.; Manley, J.; Pearlman, B. A.; Wells, A.; Zaks, A.; Zhang, T. Y. (Green Chem., 2007)

(untitled) - Thayer, A. M. (Chem. Eng. News, 2011)

(untitled) - Pattabiraman, V. R.; Bode, J. W. (Nature, 2011)

(untitled) - Patel, P. (Chem. Eng. News, 2017)

(untitled) - Declerck, V.; Nun, P.; Martinez, J.; Lamaty, F. (Angew. Chem., Int. Ed., 2009)

(untitled) - Hernández, J. G.; Juaristi, E. (J. Org. Chem., 2010)

(untitled) - Štrukil, V.; Bartolec, B.; Portada, T.; Đilović, I.; Halasz, I.; Margetić, D. (Chem. Commun., 2012)

(untitled) - Bonnamour, J.; Métro, T.-X.; Martinez, J.; Lamaty, F. (Green Chem., 2013)

(untitled) - Duangkamol, C.; Jaita, S.; Wangngae, S.; Phakhodee, W.; Pattarawarapan, M. (RSC Adv., 2015)

(untitled) - Porte, V.; Thioloy, M.; Pigoux, T.; Métro, T.-X.; Martinez, J.; Lamaty, F. (Eur. J. Org. Chem., 2016)

(untitled) - Gonnet, L.; Tintillier, T.; Venturini, N.; Konnert, L.; Hernandez, J.-F.; Lamaty, F.; Laconde, G.; Martinez, J.; Colacino, E. (ACS Sustainable Chem. Eng., 2017)

(untitled) - Landeros, J. M.; Juaristi, E. (Eur. J. Org. Chem., 2017)

(untitled) - Hernández, J. G.; Ardila-Fierro, K. J.; Crawford, D.; James, S. L.; Bolm, C. (Green Chem., 2017)

(untitled) - Datta, S.; Sood, A.; Török, M. (Curr. Org. Synth., 2011)

Ball Milling Towards Green Synthesis: Applications, Projects - Métro, T.-X.; Colacino, E.; Martinez, J.; Lamaty, F. (Amino Acids and Peptides in Ball Milling, 2015)

Mechanochemical Organic Synthesis - Margetić, D.; Štrukil, V. (Carbon–Nitrogen Bond-Formation Reactions, 2016)

(untitled) - Li, H.; Du, Z.; Lopes, D. H. J.; Fradinger, E. A.; Wang, C.; Bitan, G. (J. Med. Chem., 2011)

(untitled) - Zheng, X.; Wu, C.; Liu, D.; Li, H.; Bitan, G.; Shea, J.-E.; Bowers, M. T. (J. Phys. Chem. B, 2016)

(untitled) - Dev, D.; Palakurthy, N. B.; Thalluri, K.; Chandra, J.; Mandal, B. (J. Org. Chem., 2014)

(untitled) - Đud, M.; Margetić, D. (Int. J. Org. Chem., 2017)

Peptide Synthesis and Applications - Amblard, M.; Fehrentz, J.-A.; Martinez, J.; Subra, G. (Fundamentals of Modern Peptide Synthesis, 2005)

(untitled) - Jad, Y. E.; Khattab, S. N.; de la Torre, B. G.; Govender, T.; Kruger, H. G.; El-Faham, A.; Albericio, F. (Eur. J. Org. Chem., 2015)

(untitled) - Cliffe, M. J.; Mottillo, C.; Stein, R. S.; Bučar, D.-K.; Friščić, T. (Chem. Sci., 2012)

(untitled) - Cinčić, D.; Brekalo, I.; Kaitner, B. (Chem. Commun., 2012)

(untitled) - Lim, X. (Nature, 2015)

(untitled) - Đud, M.; Magdysyuk, O. V.; Margetić, D.; Štrukil, V. (Green Chem., 2016)

(untitled) - Sheldon, R. A. (Chem. Ind. (London), 1992)

(untitled) - Sheldon, R. A. (Green Chem., 2007)

(untitled) - Sheldon, R. A. (Green Chem., 2017)

(untitled) - Métro, T.-X.; Bonnamour, J.; Reidon, T.; Duprez, A.; Sarpoulet, J.; Martinez, J.; Lamaty, F. (Chem. – Eur. J., 2015)

(untitled) - Kumar, A.; Jad, Y. E.; El-Faham, A.; de la Torre, B. G.; Albericio, F. (Tetrahedron Lett., 2017)

(untitled) - Jad, Y. E.; Govender, T.; Kruger, H. G.; El-Faham, A.; de la Torre, B. G.; Albericio, F. (Org. Process Res. Dev., 2017)

(untitled) - Lawrenson, S.; North, M.; Peigneguy, F.; Routledge, A. (Green Chem., 2017)

(untitled) - Lawrenson, S. B.; Arav, R.; North, M. (Green Chem., 2017)

(untitled) - Erickson, B. E. (Chem. Eng. News, 2015)